2005
DOI: 10.1080/09540090500140958
|View full text |Cite
|
Sign up to set email alerts
|

Biologically plausible visual homing methods based on optical flow techniques

Abstract: Insects are able to return to important places in their environment by storing an image of the surroundings while at the goal, and later computing a home direction from a matching between this 'snapshot' image and the currently perceived image. Very similar ideas are pursued for the visual navigation of mobile robots. A wide range of different solutions for the matching between the two images have been suggested. This paper explores the application of optical flow techniques for visual homing. The performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
104
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 52 publications
0
104
0
1
Order By: Relevance
“…Visual homing methods received attention from neuroethology as models for the navigation abilities of social insects and from robotics as computationally cheap building blocks for topological approaches to map building and navigation (Franz et al 1998a). Since these methods have been extensively reviewed in recent publications (Vardy and Möller 2005;Zeil et al 2003;Franz and Mallot 2000), we restrict ourselves to the brief classification shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Visual homing methods received attention from neuroethology as models for the navigation abilities of social insects and from robotics as computationally cheap building blocks for topological approaches to map building and navigation (Franz et al 1998a). Since these methods have been extensively reviewed in recent publications (Vardy and Möller 2005;Zeil et al 2003;Franz and Mallot 2000), we restrict ourselves to the brief classification shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…In block matching, the matching is based on the pixel-by-pixel distance between two rectangular regions in two images, in intensity matching, the block is reduced to a single pixel, and gradient matching searches for the best-matching gradient (Vardy and Möller 2005). Differential flow methods are derived from Taylor approximations of correspondence equations between intensities (first-order) or between gradients (second-order) under the assumption of small shifts (Barron et al 1994).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations